2015
DOI: 10.1128/mbio.01498-15
|View full text |Cite
|
Sign up to set email alerts
|

Gene Loss and Error-Prone RNA Editing in the Mitochondrion of Perkinsela , an Endosymbiotic Kinetoplastid

Abstract: Perkinsela is an enigmatic early-branching kinetoplastid protist that lives as an obligate endosymbiont inside Paramoeba (Amoebozoa). We have sequenced the highly reduced mitochondrial genome of Perkinsela, which possesses only six protein-coding genes (cox1, cox2, cox3, cob, atp6, and rps12), despite the fact that the organelle itself contains more DNA than is present in either the host or endosymbiont nuclear genomes. An in silico analysis of two Perkinsela strains showed that mitochondrial RNA editing and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 77 publications
1
58
0
Order By: Relevance
“…These post‐transcriptional events are specified by hundreds of minicircle‐encoded guide (g) RNAs, which along with numerous large protein complexes produce a mere dozen mitochondrial proteins . Recent genomic and transcriptomic evidence confirms earlier predictions that uridine‐indel RNA editing is present in all Kinetoplastea , with the notable exception of petite mutants of T. brucei , who lack the mitochondrial genome as such .…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…These post‐transcriptional events are specified by hundreds of minicircle‐encoded guide (g) RNAs, which along with numerous large protein complexes produce a mere dozen mitochondrial proteins . Recent genomic and transcriptomic evidence confirms earlier predictions that uridine‐indel RNA editing is present in all Kinetoplastea , with the notable exception of petite mutants of T. brucei , who lack the mitochondrial genome as such .…”
Section: Introductionmentioning
confidence: 59%
“…Electron microscopic studies from almost 50 years ago revealed that some bodonid flagellates contain huge amounts of kinetoplast DNA. However, their size and coding capacity has only recently started to become clear . Only direct comparison with sequenced nuclear genomes, as carried out here, allows estimation of their size.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…We find no evidence for RNA-editing in E. gracilis, nor for the TAC, both of which are consistent with the presence of a mitochondrial genome composed of only short linear DNA molecules (encoding only seven different proteins) and a conventional mitochondrial mRNA transcription system . Specifically, only 14 of 51 proteins involved in RNA-editing in T. brucei (David, et al, 2015) had reciprocal best BLAST ! 13…”
Section: ! 10mentioning
confidence: 99%